2006
DOI: 10.1080/02699200500074321
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing load as a determinant of stuttering: Summary of a research programme

Abstract: The present paper integrates the results of experimental studies in which cognitive differences between stuttering and nonstuttering adults were investigated. In a monitoring experiment it was found that persons who stutter encode semantic information more slowly than nonstuttering persons. In dual-task experiments the two groups were compared in overt word-repetition and sentence-production experiments. The results of the two word-repetition experiments indicate that the speech of stuttering persons is sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
65
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 51 publications
11
65
0
1
Order By: Relevance
“…A model relating to task demands that may partially explain the data presented here has been proposed by Bosshardt (2006). In a series of investigations, Bosshardt and colleagues have found that adults who stutter produce either shorter and less grammatically complex utterances or more disfluency under dual task conditions, in which attention is divided (e.g., Bosshardt, 2002;Bosshardt, Ballmer, & de Nil, 2002).…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…A model relating to task demands that may partially explain the data presented here has been proposed by Bosshardt (2006). In a series of investigations, Bosshardt and colleagues have found that adults who stutter produce either shorter and less grammatically complex utterances or more disfluency under dual task conditions, in which attention is divided (e.g., Bosshardt, 2002;Bosshardt, Ballmer, & de Nil, 2002).…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%
“…These investigations point to differences in cognitive processing in people who stutter and normally fluent speakers. Bosshardt (2006) has suggested that people who stutter are vulnerable to increased processing loads, perhaps due to an overlap in functioning in speech-motor and speech planning areas of the brain. Looking at the data from the current study from the viewpoint of Bosshardt's model, it could be said that the longer utterances in section B required more cognitive resources to generate than the shorter utterances in Section A, with more disfluencies resulting.…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of increased length and syntactic complexity on the fluency of young children lends support for psycholinguistic theories of stuttering, which suggest that syntactic, lexical, phonological, or suprasegmental aspects of speech production may play a role in the expression of stuttering (Bernstein Ratner, 1997). In addition, in studies of adults who stutter, it has been proposed that increased processing demands, such as those associated with increased length and /or linguistic complexity, may lead to fluency disruptions (Bosshardt, 2006). Others have explored the relationship between linguistic encoding difficulties and related motor instabilities, with outcomes suggesting that the motoric stability of persons who stutter may be uniquely vulnerable to increases in linguistic complexity .…”
mentioning
confidence: 99%